Innovative activity in the field of recreation and tourism (Eurasian Research Bulletin, 2022)
In this article, specific features of the implementation of innovative activity in the field of tourism and recreation, theoretical views and approaches to the introduction of innovations in the field, classification of innovations in tourism, factors of increasing innovative activity in the field of tourism and recreation are studied.